From Grief to Grievance: Combined Axes of Personal and Collective Grief Among Black Americans - Wilson, Da'Mere T.; O'Connor, Mary-Frances (Frontiers in Psychiatry, 2022)
In the current article, we argue that the current conceptualization of grief as ‘the acute pain that accompanies the loss of a loved one’ is too narrow in scope. Specifically, our current conceptualization of grief fails to account for the various ways in which grief is manifested amongst Black Americans. Throughout the article, we explore how the history of the racialization of Black people in America has resulted in a unique experience of loss, grief, and bereavement which previous research has largely failed to elucidate. Additionally, we explore how grief catalyzes political and social action. The article also proposes a novel theoretical conceptualization of personal and collective grief to deepen our conceptualization of grief amongst Black Americans. Finally, we posit that we must also consider how to further research this collective grief to increase our understanding of it and to account for similar phenomena that may exist in communities who’ve had similar experiences (e.g., Indigenous peoples in the Americas, Dalits in India).